Age at menarche and later-life diabetes risk in Chinese women - Shanshan Chen; Pengyi Chen; Min Wu; Xiaohao Hu; Lianhui Chen (Medicine, 2026)
Early menarche has been implicated in increased cardiometabolic risk, including type 2 diabetes, but evidence from Asian populations remains limited and inconsistent. We aimed to investigate the association between age at menarche and incident diabetes among Chinese women using data from a nationwide population-based longitudinal cohort. We analyzed data from 5859 women participating in the China Health and Retirement Longitudinal Study 2011 to 2020. Age at menarche was assessed at baseline and modeled as a continuous variable and in 5 categories. Participants with baseline diabetes were excluded based on self-reported physician diagnosis, glucose-lowering medication use, or abnormal fasting glucose/glycated hemoglobin. Incident diabetes during Waves 2 to 5 was identified by physician diagnosis. Survey-weighted Cox proportional hazards models, restricted cubic splines, and subgroup analyses were applied to evaluate associations while accounting for sampling design and covariates. Over a median follow-up of 8.4 years, 732 incident diabetes cases occurred (12%). Menarche timing was not associated with diabetes onset when modeled continuously (hazard ratio = 1.01, 95% confidence interval: 0.97–1.06) or categorically, with hazard ratio across menarche groups ranging narrowly around unity. Restricted cubic splines demonstrated a flat dose-response pattern with no threshold or nonlinear trend ( P for nonlinearity = .944). Results remained unchanged across age, body mass index, and residence subgroups. In this large prospective study of middle-aged and older Chinese women, age at menarche was not detectably associated with incident self-reported physician-diagnosed diabetes in later life.